Oral health status of smoker: a 6 months follow-up - Ghazali, Aini Fatimah; Ismail, Ahmad Faisal; Daud, Azlina (Elsevier, 2019)
The objective of this study was to evaluate oral health of cigarette smokers based on time effect. This observational study involved 40 participants. Oral health examination was conducted according to the World Health Organization (WHO) criteria. Dental caries was evaluated using the DMFT index, while the periodontal parameters assessed using plaque, gingivitis, gingival bleeding, and calculus indices. The results were compared using Paired t-test and Wilcoxon Signed Ranks Test, the outcomes of which were significant for the Plaque Index (p = 0.042), and Bleeding Index (p = 0.037) of periodontal health. There were no significant differences in the other periodontal health parameters, as the p values of the Gingival Index, Calculus Index and DMFT Index were 0.309, 0.586 and 0.500 respectively. In conclusion, cigarettes had potentially detrimental effects in terms of time effect on oral health.